2013
DOI: 10.3109/0284186x.2013.770165
|View full text |Cite
|
Sign up to set email alerts
|

Harvest for health gardening intervention feasibility study in cancer survivors

Abstract: Background Cancer survivors are at increased risk for second malignancies, cardiovascular disease, diabetes, and functional decline. Evidence suggests that a healthful diet and physical activity may reduce the risk of chronic disease and improve health in this population. Methods We conducted a feasibility study to evaluate a vegetable gardening intervention that paired 12 adult and child cancer survivors with Master Gardeners to explore effects on fruit and vegetable intake, physical activity, quality-of-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 29 publications
0
98
0
Order By: Relevance
“…To our knowledge, these two investigations plus the initial pilot study of 12 subjects [7], are the first home-based vegetable gardening intervention trials among cancer survivors or any patient population. Both BBCS and ASCS provide cancer survivors with the opportunity to gain skills that promote lifelong changes in their lifestyle behaviors and may ultimately improve their overall health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, these two investigations plus the initial pilot study of 12 subjects [7], are the first home-based vegetable gardening intervention trials among cancer survivors or any patient population. Both BBCS and ASCS provide cancer survivors with the opportunity to gain skills that promote lifelong changes in their lifestyle behaviors and may ultimately improve their overall health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Harvest for Health was first conducted as a single-arm pilot study with 12 adult and child cancer survivors [7]. Results suggested that the vegetable gardening intervention was associated with promising benefit, not only on improving the diet, but also on physical functioning, and physical activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited available literature relies on qualitative reports from various therapy gardens and single attempts to integrate nature activities into other types of supportive care or therapeutic modalities [21,22]. Although these accounts contribute lower level evidence than clinical trials, they are successful in eliciting cancer patients' subjective experiences with nature and reveal unique patient needs.…”
Section: Literature Reviewmentioning
confidence: 99%